The reasons for its effectiveness, however, remain in dispute—A tribute to Irving Kirsch - Gaab, Jens (Frontiers in Psychology, 2022)
Irving Kirsch’s work spans over four decades and provided science and clinical practice with as much invaluable insights in the inner workings of treatments as it also provided us and pa-tients with their rights and our duties. Here, two early publications of Irving Kirsch on the topic of psychotherapy and its relation to placebo are revised and put in both a historical as well as contemporary context in order to pay tribute to the work of Irving Kirsch.